Chemical composition of purslane (Portulaca oleracea L.) and anti-inflammatory activity of its lipid components (The Philippine Journal of Crop Science, 2012)
The chemical composition of purslane (Portulaca oleracea L.) locally grown and known as ‘olasiman’ was determined. Inductively coupled plasma spectroscopy and proximate analysis of the edible portion of mature plants revealed higher mineral, protein, fat, and fiber contents compared to common leafy vegetables like cabbage and lettuce. Gas chromatographic analysis of the oil extract revealed 17.00-+ 0.33% and 5.08 +- 0.49% of the omega-3 fatty acids a-linolenic acid and docosahexaenoic acid, respectively. Phytosterols, a-tocopherol, and squalene were also quantified at 6.52+- 0.44 mg, 9.05+- 0.04mg, and 115.0 +-2.0 ug per 100 g fresh weight, respectively. The major phytosterols were then isolated and quantified using argentation thin layer chromatography. B-sitosterol was identified as the dominant sterol component. An in vivo chorioallantoic membrane 9CAM) assay, which utilized the highly vascularized CAM as biological test surface, was done to evaluate the anti-inflammatory activity of purslane. Purslane oil and its saponifiable and ansaponifiable fractions exhibited 44-49% inhibition of the irritation caused by sodium dodecyl sulfate when applied to CAM at 15-150 ug. The anti-inflammatory activity of purslane can be attributed to the presence of the aforementioned phytochemicals. This information is vital to promote the plant as a functional food. As a functional food, it should contain physiologically active components that provide health benefits beyond basic nutrition.